Comprehensive Review of the Literature to Teach Campus Navigation to Young Adults with Intellectual and Developmental Disabilities - Richter, Sharon; Uphold, Nicole (Journal of Inclusive Postsecondary Education, 2020)
Young adults with intellectual and developmental disabilities (I/DD) experience unique challenges as they transition to living and learning on a college campus, including independent campus navigation. The purpose of this study was to present the results of a comprehensive literature review of interventions designed to improve campus navigation among young adults with I/DD. A second purpose of this review is to present the practical considerations of the interventions to support informed instructional decisions among practitioners.